2015
DOI: 10.1055/s-0034-1395384
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Rapid Prototyping and Intraoperative Imaging in Orbital Reconstruction

Abstract: In Christchurch Hospital, rapid prototyping (RP) and intraoperative imaging are the standard of care in orbital trauma and has been used since February 2013. RP allows the fabrication of an anatomical model to visualize complex anatomical structures which is dimensionally accurate and cost effective. This assists diagnosis, planning, and preoperative implant adaptation for orbital reconstruction. Intraoperative imaging involves a computed tomography scan during surgery to evaluate surgical implants and restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…[ 54 ] Validation Study Japan Cranial Surgery Craniotomy Training, Simulation 2016 Lim SH et Al. [ 55 ] Validation Study Korea Macillo-Facial Surgery Mandible reconstruction Planning 2015 Pacione D et al [ 56 ] Pilot Study USA Maxillofacial Surgery Deformity of the skull base and craniovertebral junction Planning 2015 Chan HHL et al [ 57 ] Case Series Canada Maxillofacial Surgery Head and neck surgery Training, Simulation 2015 Dickinson KJ et al [ 58 ] Case Report USA Maxillofacial Surgery Endoscopic resection in esophagus Planning 2015 Hochman JB et al [ 59 ] Comparative Study Canada Maxillofacial Surgery Mastoidectomy and skull base surgery Training 2015 Cohen J et al [ 60 ] Validation Study USA Maxillofacial Surgery Mastoidectomy Training 2015 Lim C et al [ 17 ] Case Series Australia - New Zealand Maxillofacial Surgery Orbital reconstruction Planning 2015 Rose AS et al [ 61 ] Case Report USA ENT Surgery Mastoidectomy Planning, Simulation 2015 Ernoult C. et Al. [ 62 ] Case Series France Maxillofacial Surgery ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 54 ] Validation Study Japan Cranial Surgery Craniotomy Training, Simulation 2016 Lim SH et Al. [ 55 ] Validation Study Korea Macillo-Facial Surgery Mandible reconstruction Planning 2015 Pacione D et al [ 56 ] Pilot Study USA Maxillofacial Surgery Deformity of the skull base and craniovertebral junction Planning 2015 Chan HHL et al [ 57 ] Case Series Canada Maxillofacial Surgery Head and neck surgery Training, Simulation 2015 Dickinson KJ et al [ 58 ] Case Report USA Maxillofacial Surgery Endoscopic resection in esophagus Planning 2015 Hochman JB et al [ 59 ] Comparative Study Canada Maxillofacial Surgery Mastoidectomy and skull base surgery Training 2015 Cohen J et al [ 60 ] Validation Study USA Maxillofacial Surgery Mastoidectomy Training 2015 Lim C et al [ 17 ] Case Series Australia - New Zealand Maxillofacial Surgery Orbital reconstruction Planning 2015 Rose AS et al [ 61 ] Case Report USA ENT Surgery Mastoidectomy Planning, Simulation 2015 Ernoult C. et Al. [ 62 ] Case Series France Maxillofacial Surgery ...…”
Section: Resultsmentioning
confidence: 99%
“…In dentistry, bone models were more frequently used for simulating dental implant placement [ 30 , 41 , 81 ]. In oral and maxillofacial surgery, the models were more frequently used for planning a bone reconstruction [ 15 – 17 , 36 , 40 , 47 , 50 , 53 , 72 ] or a tumor removal [ 18 , 49 , 56 ]. The models prepared for ENT surgery were mostly used for training surgical temporal access [ 10 , 31 , 52 , 63 68 , 85 , 87 ] and mastoidectomy [ 39 , 51 , 59 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomical models can be used for implant shaping in maxillofacial surgery, a topic that was discussed in nine studies [ 33 41 ]. Five papers mentioned time reduction as advantage [ 33 , 36 , 38 40 ]. Eight studies concluded that printed models provide good anatomical representations and nine studies mentioned improved surgical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies concluded that printed models provide good anatomical representations and nine studies mentioned improved surgical outcomes. Two studies mentioned exposure to ionizing radiation [ 36 , 41 ] and two mentioned increased costs [ 39 , 41 ].…”
Section: Resultsmentioning
confidence: 99%